The Effect of Family Psychological Dynamics on Children's Achievement Outcomes: A Meta-Analysis Study - Dogan, Serhan (International Journal on Studies in Education, 2025)
Family psychological dynamics play a critical role in children's academic, social, and emotional development. This meta-analysis examined the effect of family psychological dynamics on children's achievement outcomes. Relevant studies were identified by searching the YÖK Thesis and ProQuest databases in January 2025. The search yielded 97 dissertations, 32 of which could be included in the meta-analysis. In this study, 32 dissertations were combined and a sample group of 7928 people was obtained. The results of the analysis using the random effects model showed that psychological dynamics within the family had a low-level effect on children's achievement outcomes. Country, psychological dynamics, year of publication, and data collection instrument were found to be moderating variables. Subject based on academic achievement was not found to be a moderator variable.